Estimating Seafloor Topography of the South China Sea Using SWOT Wide-Swath Altimetry Data - Fengshun Zhu; Jinbo Li; Yang Li; Jianqiao Xu; Jinyun Guo; Jiangcun Zhou; Heping Sun (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
The surface water and ocean topography (SWOT) wide-swath altimetry satellite was launched in December 2022. The performance of novel wide-swath altimetry in seafloor topography modeling needs to be evaluated. This study utilized 15 cycles of SWOT Level-3 product to construct seafloor topography model of the South China Sea by linear regression analysis. The root mean square error of the difference between the model and shipborne bathymetry at checkpoints is about 120 m, which is 20 m better than topo_27.1 and DTU18BAT, and 40 m better than ETOPO1. First, the effects of the shipborne bathymetry at control points and priori bathymetry model in different topography-gravity scaling factor estimation strategies [A: using robust least squares (RBLSQ) to estimate regional scaling factor; B: using ratio method to calculate scaling factors at control points; C: using the moving window method and RBLSQ to obtain scaling factor grids.] on SWOT seafloor topography modeling are explored. We find that the control point number barely affects strategy A/C but significantly affects strategy B, while the priori bathymetry model mainly affects strategy C. Then, the three strategies are applied to the traditional radar altimetry gravity anomaly, and the results are compared with the SWOT-derived seafloor topography. The results show that incorporating SWOT data can improve the accuracy of seafloor topography estimation by about 7 m, and improve the power spectral density in the wavelength range about 10–20 km, which can help to reveal more detailed topography information.